KURIKULUM FLEKSIBEL MADRASAH NIZAMIYAH: ADAPTASI KREATIF PENDIDIKAN ISLAM KLASIK UNTUK PAI KONTEMPORER: Adaptasi Kreatif Pendidikan Islam Klasik untuk PAI Kontemporer - Abdus Salam; Edi Junaidi Ds; Sugeng Listyo Prabowo (Najah Bestari, 2025)
This article explores the relevance and potential adaptation of the Nizamiyah Madrasa curriculum within the context of contemporary Islamic Religious Education (PAI). Established in the 11th century, the Nizamiyah system is recognized as a structured, flexible, and integrative model of Islamic education that successfully produced renowned scholars and contributed significantly to the development of Islamic civilization. This study employs a qualitative method with a library research approach, analyzing historical and educational literature related to Islam ic curriculum development. The findings indicate that current PAI faces several challenges, including centralized curriculum design, cognitively biased evaluation, fragmented disciplines, and limited teacher autonomy. By adapting the core principles of the Nizamiyah curriculum such as modular structures, interdisciplinary integration, the teacher's role as a spiritual guide, and holistic evaluation PAI can evolve into a more contextual, transformative, and future-oriented educational system. Nizamiyah curriculum such as modular structures, interdisciplinary integration, the teacher's role as a spiritual guide, and holistic evaluation PAI can evolve into a more contextual, transformative, and future-oriented educational system. Reinvigorating these classical educational values offers a promising alternative for reforming PAI to better meet the needs of contemporary society.